2019
DOI: 10.1016/j.pacfin.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Political uncertainty and Stock returns: Evidence from the Brazilian Political Crisis

Abstract: This paper examines the effect of political uncertainty on stock returns, exploiting an exogenous shock to political stability in Brazil. In May, 2017, a conversation between Brazil's President and a businessman was bugged by Brazilian Police and leaked to the media. This led to sudden political instability and a collapse in the equity market. We decompose the cross-sectional variation of abnormal returns around this event and investigate whether corporate political connections and exposure to foreign capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 51 publications
1
25
1
4
Order By: Relevance
“…Often the watch-dog authorities themselves have been implicated thus paradoxically encouraging a mistrustful mindset towards the legitimacy of sanctions-leading to a vicious and spiralling cycle of corruption. For example, in Brazil, the state-owned company Petrobras was implicated in a major corruption scandal which included top officials including the President ( Hillier and Loncan, 2019 ); this affected the equity markets adversely. There is a recognition that not just the legal framework, but the cultural mindset should change; worryingly, corruption has persisted despite historical and legislative attempts to curb it.…”
Section: Brics: An Overviewmentioning
confidence: 99%
“…Often the watch-dog authorities themselves have been implicated thus paradoxically encouraging a mistrustful mindset towards the legitimacy of sanctions-leading to a vicious and spiralling cycle of corruption. For example, in Brazil, the state-owned company Petrobras was implicated in a major corruption scandal which included top officials including the President ( Hillier and Loncan, 2019 ); this affected the equity markets adversely. There is a recognition that not just the legal framework, but the cultural mindset should change; worryingly, corruption has persisted despite historical and legislative attempts to curb it.…”
Section: Brics: An Overviewmentioning
confidence: 99%
“…As stated by the study of Barro (1991), in periods of political turbulence, entrepreneurs with a risk-averse perspective are likely to shift their investments to other countries that offer more relative safety and less risk. More recent studies by Wang (2019), Hillier and Loncan (2019) and Charfeddine and Al Refai (2019) have indicated that stock markets are adversely effected by rising political tension in both domestic markets and in the international arena.…”
mentioning
confidence: 99%
“…While this study focused on the impact of cross-country stock market co-movements, future research might investigate the impact on the industry level in order to test whether diversification across industries might provide better diversification benefits and therefore a hedge against market downturns. Lastly, it might be of interest to compare the trade war with past political turmoil, for example Hillier and Loncan (2019) examining political uncertainty and stock market reaction in Brazil. 9(1), 21-30, 2019 Tariffs on $34 billion Chinese products were imposed.…”
Section: Resultsmentioning
confidence: 99%